Emerging Asia LNG demand - Mike Fulwood; James Henderson; Ieda Gomes; Martin Lambert; Jack Sharples (The Oxford Institute for Energy Studies, 2020)
Since the birth of the LNG industry, Asia has been the key market, providing high value, reliable demand. The 3 foundation markets of Japan, South Korea and Taiwan have been joined more recently by China and India to form the "big 5" which is often the focus for much analysis and comment. However, it would be wrong to ignore the smaller, emerging Asian LNG markets. By considering the 10 most significant emerging Asian markets, this report demonstrates that when combined, they have potential LNG demand over the next 2 decades as the combination of India and China. Like all demand forecasts, whether that potential is achievable is, however, depends on overcoming some significant challenges, as discussed in the report. In addition, these smaller countries offer a diversity of analytical interest. Malaysia and Indonesia are LNG exporters, now looking to become significant importers. Thailand, Pakistan, Bangladesh, Vietnam and the Philippines all see LNG as needed to supplement declining domestic gas production. Myanmar started LNG imports to address a power crisis, and Hong Kong and Singapore are largely driven by environmental and security of supply concerns. With a chapter on each country and detailed breakdown of the forecasts generated by our World Gas Model, the document provides a useful reference of current perceptions of future prospects in those emerging LNG markets.
Keywords: 330; Asia; Bangladesh; Hong Kong; Indonesia; LNG; Malaysia; Myanmar; NG 162; Pakistan; Philippines; Singapore; Thailand; Vietnam; World Gas Model